Stratifikasi Sosial Komunitas Bajo di Kabupaten Bone Sulawesi Selatan - Syamsul Bakhri Gaffar (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2023)
This study aims to reveal the social stratification of the Bajo community. This study was designed using a qualitative approach. The types and sources of data used consist of primary data and secondary data. Primary data is collected from main sources, namely from Bajo community leaders. Secondary data was collected from writings that were relevant to this research. Data collection was carried out through: (a) in-depth interviews with a number of informants using purposive, triangulation and snowball techniques, (b) observation, and (c) documentation. Data and information were analyzed through qualitative analysis. This study reveals that in the Bajo community there are four social stratifications, namely: (1) Lolo Bajo, namely the aristocratic class who have been leaders in the Bajo community for generations; (2) Punggawe, also including the descendents of the Bajo nobility who are one of the customary positions responsible for fostering security and order in the Bajo community; (3) Anak Bajo, are a group of ordinary people who come from the descendants of most people; and (4) Ate Bajo, namely the Bajo community group that is considered the lowest in social stratification. In practice, this group is no longer found except symbolically, such as at weddings because they are considered to be contrary to the teachings of Islam that they adhere to. Apart from these four social stratifications, the Bajo community also recognizes a patron-client social layering system, namely the relationship pattern. Punggawe-Sawi which is also a social coating.